PENEGAKAN HUKUM PERKREDITAN BANK DALAM RANGKA MENUNJANG KEGIATAN PERBANKAN DI INDONESIA - , Zainul Arifin, SE; , Prof. Emmy Pangaribuan S.H. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In accordance with the rate of economic growth and development movement of a nation, financial institutions grew by a variety of alternative services offered. The financial institution which is the intermediary institutions of the party who have excess funds (surplus of funds) with those who lack funds, has a function as an intermediary financial community, financial institutions, as well as an institution or another institution and there are virtually in the middle of society. One of the bank's business in pebankan activities to support the development of national economy in Indonesia are helping with the implementation of bank credit to the people of Indonesia in developing a business which is also meant to help the development of the nation's economy. Mischief of the bank by not heeding the principles of prudence (prudential principle) in terms of loan would clearly harm the health of banking and shake the national economy. Problems, Are funds disbursed by the bank as a form of credit to customers who done without prudential banking activities can harm the health? How legal efforts made by the aggrieved parties in the provision of credit with a guarantee by the Bank. The purpose of research to find out the credit process and efforts by law if any party is aggrieved with the credit. Research Methods, juridical normative. In conclusion, the bank should exercise caution in every withdrawing the funds in the form of loans to both individuals and corporate community. Efforts by law if any party is aggrieved by the granting of loans to the courts.